PARP7 mono-ADP-ribosylates the agonist conformation of the androgen receptor in the nucleus. Issue 15 (13th August 2021) - Kamata, Teddy; Yang, Chun-Song; Paschal, Bryce M.
Abstract : We recently described a signal transduction pathway that contributes to androgen receptor (AR) regulation based on site-specific ADP-ribosylation by PARP7, a mono-ADP-ribosyltransferase implicated in several human cancers. ADP-ribosylated AR is recognized by PARP9/DTX3L, a heterodimeric complex that contains an ADP-ribose reader (PARP9) and a ubiquitin E3 ligase (DTX3L). Here, we have characterized the cellular and biochemical requirements for AR ADP-ribosylation by PARP7. We found that the reaction requires nuclear localization of PARP7 and an agonist-induced conformation of AR. PARP7 contains a Cys3 His1 -type zinc finger (ZF), which also is critical for AR ADP-ribosylation. The Parp7 ZF is required for efficient nuclear import by a nuclear localization signal encoded in PARP7, but rescue experiments indicate the ZF makes a contribution to AR ADP-ribosylation that is separable from the effect on nuclear transport. ZF mutations do not detectably reduce PARP7 catalytic activity and binding to AR, but they do result in the loss of PARP7 enhancement of AR-dependent transcription of the MYBPC1 gene. Our data reveals critical roles for AR conformation and the PARP7 ZF in AR ADP-ribosylation and AR-dependent transcription.